1984
DOI: 10.1128/aac.26.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative extraction of amphotericin B from serum and its determination by high-pressure liquid chromatography

Abstract: Therapeutic concentrations of amphotericin B in serum were measured by reversed-phase liquid chromatography with detection at 386 nm. Complete recovery of the drug and the internal standard from a l-ml serum sample was achieved by pretreating the sample with guanidine hydrochloride and extracting it with a disposable reversed-phase phenyl extraction column. The method was sensitive to 0.005 ,ug of amphotericin B per ml and linear to at least 5 ,ug/ml. Coehicients of variation were 4.8% within-run and 6.3% betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Thus, it is reasonable to assume that therapeutic regimens should aim at achieving plasma drug levels of 1-2 gg/ml. Determination of drug concentrations in serum is possible using HPLC [2,8,17,18,21,23,31,34], but this method cannot be employed for routine analyses of a large number of samples. An alternative method involving spectrophotometric determination of Amphotericin B concentrations in acetonitrile serum extracts has been reported [37].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is reasonable to assume that therapeutic regimens should aim at achieving plasma drug levels of 1-2 gg/ml. Determination of drug concentrations in serum is possible using HPLC [2,8,17,18,21,23,31,34], but this method cannot be employed for routine analyses of a large number of samples. An alternative method involving spectrophotometric determination of Amphotericin B concentrations in acetonitrile serum extracts has been reported [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, AB in spiked sera stored at 27, 4, Ϫ20, and Ϫ70ЊC was found to have shelf half-lives of 21 h at 27ЊC and 20 days at 4ЊC, but no change was found in samples frozen at Ϫ70ЊC (1). It was not discussed previously (1) whether these samples were protected from light. Therefore, on the basis of previous data, the serum samples were immediately frozen and protected from light until use.…”
Section: Discussionmentioning
confidence: 99%
“…The Other investigators, using similar sample preparation, reported recovery rates of 98.6-100% [9], 75-80% [lo] and 53-61% [ll]. Bach [12] argued that there are at least two disadvantages to the protein precipitation technique. First, precipitation is slow and incomplete and may interfere with the assay or clog the column.…”
Section: Discussionmentioning
confidence: 99%